PERAN INTERVENSI DIGITAL DALAM EDUKASI PROMOSI KESEHATAN GIGI DAN MULUT MASYARAKAT: SYSTEMATIC LITERATURE REVIEW - Meyrinda Tobing; Ibnu Gunawan; Iin Indah Aris Wati; Joko Widyastomo (LPPM STIKes Mitra Adiguna, 2026)
Oral health remains a global burden affecting more than 3.5 billion individuals worldwide. Despite the rapid advancement of digital technology, its role as a medium for oral health promotion and education has not been systematically mapped. This study aimed to analyze the role of digital interventions in oral health education and promotion through a bibliometric-based Systematic Literature Review (SLR). Data were collected from the ScienceDirect database using the PRISMA method with the keywords Digital Media AND Oral AND Community and Dental Health Promotion AND Community, yielding 529 selected articles published between 2016 and 2026. Analysis was conducted using VOSviewer 1.6.20 through a term co-occurrence approach, resulting in 34 items grouped into four clusters. Findings revealed that digital interventions effectively improve oral health knowledge and behavior. The four clusters encompassed digital literacy and behavior change, the burden of dental disease in children, web-based program implementation, and family access barriers and perceptions. Temporal trend analysis indicated a paradigm shift from descriptive-epidemiological toward technology-based interventionist approaches. A research gap was identified regarding the role of social mediators in digital dental service adoption. These findings highlight the urgency of developing protocolized, inclusive, and contextually appropriate digital interventions to sustainably improve community oral health.